Analisis Kepailitan PT Asuransi Jiwasraya Persero dalam Perspektif Perlindungan Konsumen dan Kepastian Hukum Bagi Kreditor - Hania Arvalia; Elisatris Gultom; Sudaryat Sudaryat (Journal of Sharia and Legal Science, 2025)
The bankruptcy of insurance companies is a complex issue involving the interests of consumers as policyholders and creditors who demand legal certainty. This study aims to analyze bankruptcy issues within the Indonesian insurance industry through a case study of PT Asuransi Jiwasraya (Persero), with a focus on legal protection for consumers and the assurance of legal certainty for creditors. The research method employed is normative juridical, using a statutory and case study approach. The findings indicate that the resolution mechanism for Jiwasraya’s default did not follow the bankruptcy process as stipulated in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU), but was instead resolved through state intervention and restructuring via a state-owned insurance holding company. This has created a legal dilemma regarding the suboptimal protection of consumer rights and the weakened position of creditors in the settlement process. On the other hand, the authority of the Financial Services Authority (Otoritas Jasa Keuangan/OJK) in supervising and intervening in troubled insurance companies becomes a crucial aspect that requires clearer regulatory provisions. Therefore, a reformulation of policies and a more comprehensive legal framework is needed to ensure a balanced protection of consumers and legal certainty for creditors in bankruptcy cases involving insurance companies.